Performance of thermoelectric conversion device with power management module based on shallow soil-air temperature difference. (December 2021) - Ga, Latai; Zhang, Zhe; Xu, Daochun; Li, Wenbin
Abstract: The development of wireless sensor technology has provided an alternative research direction for monitoring of the Internet of Things. However, the practical application of wireless sensor technology is currently constrained by power supply requirements and the rather laborious task of replacing or maintaining the sensor batteries. In this paper, a wireless node power supply system based on the temperature difference between the shallow soil-air was designed. The distinguishing features of this device include application of a gravity heat pipe, thermoelectric generators (TEGs), copper heat fins, and radiators to absorb, transfer and convert the thermal energy. The study measured the performance of the proposed device in an experimental outdoor platform, the results show that in the 8 h monitoring of a day, the temperature difference of thermoelectric device ranged from 12.96k to 24.69k, the peak voltage of the device was 722.13 mV and the peak power was 3.62 mW when the proposed device was at the optimal external load. Furthermore a power management system was designed to increase the output voltage and eventually store it in the supercapacitor. In conclusion, The system provides an effective mechanism for solving the energy supply problem of wireless sensor.